2021
DOI: 10.7759/cureus.14888
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Tamponade Secondary to Influenza B Infection

Abstract: Every year, Influenza infection contributes to significant morbidity and mortality carrying a huge economic burden. Extra-pulmonary manifestations are increasingly being recognized. We present a 29-year-old woman with acute pericarditis and cardiac tamponade requiring emergent pericardiocentesis secondary to Influenza B infection. Although very rare in relation to Influenza B infection, the pericardial disease can occur during the acute infection or as a post-viral syndrome. Considering pericardial disease in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Our literature review identified 75 unique cases (55 adult and 20 pediatric patients) from 56 case reports, and 5 case series describing 2 to 8 patients each, published from 1959 through 2021 [ 2 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 75 unique cases (55 adult and 20 pediatric patients) from 56 case reports, and 5 case series describing 2 to 8 patients each, published from 1959 through 2021 [ 2 , 12 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ,…”
Section: Resultsmentioning
confidence: 99%